Stock Market and Financial Improvement among Shareholders in Baglung - Panta, Saroj Raj; Silwal, Sudarshan (Curriculum Development Journal, 2024)
The main aim of this paper is to examine the overall change and improvement in shareholders’ lifestyle and financial health through the stock market business in Baglung. For this, a mixed method qualitative and quantitative approach was applied. Data were gathered from both primary and secondary sources. A study carried out in Baglung Municipality between March and July 2024, which included respondents and 46 investors, revealed encouraging prospects for a stock market in the region. This was supported by surveys, field observations and direct oral investigation tools interviews with staff from Deevyaa Securities Pvt. Ltd. and various investors. This study revealed promising opportunities for a stock market in Baglung. The data and information obtained from both sources were analyzed descriptively. During the data collection process, we found that shareholders had theoretical knowledge about the stock market but lacked proper awareness. There was a significant gap between people’s theoretical knowledge and their practical understanding of the stock market. Despite, this the study found a broad spectrum of positive outcomes for share market investors in the study area. The stock market faces a variety of obstacles and challenges that impede its growth. Nevertheless, by addressing these issues, there exists significant potential for expansion within the market. Awareness initiatives can play a crucial role in informing individuals about the opportunities and challenges associated with the stock market in the study area. This research will helpful for the students, researchers, and others who have an interest in this domain.